Bridging local and external knowledge for disaster risk management planning: The perceived benefit of participatory 3D modelling in Umgungundlovu District Municipality, South Africa - Wielenga, Rutger (School of Architecture, Planning and Geomatics, 2025)
There are natural hazards affecting communities all over the world. These events also take place in South Africa. South African disaster management legislation emphasises the indigenous knowledge of people who are most affected when hazards turn into disaster. Participatory GIS in the form of activities building and using three-dimensional models (P3DM) has been used internationally to enhance community engagement and to ensure better information exchange between people who live in the area and the disaster officials and consultants who currently inform decisions. P3DM was introduced in uMgungundlovu District Municipality through a progressive case study methodology with workshops in four locations introduced by municipal officials. This research focused on the officials' perceived value of using P3DM activities to enhance their standard disaster risk management practices. Lightning, fires, earthquakes and strong winds are all natural hazards experienced by people living in communities. Over a period of several generations, these people have developed knowledge local to their area that is relevant in planning to reduce the risk of disasters in their area. The disaster risk management legislation governing this planning requires the sharing of local knowledge. The implementation of the legislation and the sharing of local knowledge are challenging. Participatory three-dimensional modelling (P3DM) has been used in the Global South as a novel method to promote knowledge sharing in this context. Although this method is commonly used elsewhere in the Global South, it has not yet been used or introduced in South Africa. Through a progressive case study in four locations in uMgungundlovu District Municipality, P3DM was introduced to stakeholders in disaster planning. There was an opportunity to analyse and assess the perceived value of P3DM to stakeholders at each location. Observational case study methods including semi-structured interviews allowed data collection and analysis to assess the perceived value of P3DM. P3DM was found to add value to stakeholders already familiar with incorporating local knowledge in disaster planning. Officials and community members attending workshops where P3DM activities were introduced recognized that building models and adding LIK to the models facilitates knowledge sharing.